Pseudoaneurysms within ruptured intracranial arteriovenous malformations: diagnosis and early endovascular management. - Garcia-Monaco, R; Rodesch, G; Alvarez, H; Iizuka, Y; Hui, F; Lasjaunias, P (American Journal of Neuroradiology, 1993)
PURPOSE To draw attention to pseudoaneurysms within ruptured arteriovenous malformations and to consider their diagnostic and therapeutic features, including pitfalls and precautions needed for safe embolization.METHODS Radiologic and clinical charts of 189 patients who bled from intracranial arteriovenous malformations were retrospectively reviewed.RESULTS Fifteen of the 189 (8%) were found to have pseudoaneurysms. Nine of the pseudoaneurysms were arterial, six were venous. In the early period following hemorrhage, nine patients were treated conservatively. The other six were treated with surgery (one case) or embolization (five cases) because urgent intervention was required. The clinical outcome for both conservative and interventional groups was generally favorable, but one patient in the conservative group died of a rebleed. In the patients who underwent embolization, the fragile nature of the pseudoaneurysm made it necessary to first embolize the artery feeding it. Embolization with particles was considered hazardous. Instead, free-flow (nonwedged) N-butyl-cyanoacrylate embolization proved safe and effective in treating both the pseudoaneurysms and arteriovenous malformations in these cases.CONCLUSIONS This study highlights the importance of recognizing pseudoaneurysms in such patients and the importance of using free-flow liquid adhesive material on the artery feeding the pseudoaneurysm if embolization is required.